The need for simple dynamic equations to describe plant competition - Mutsaers, H.J.W. (Oxford University Press, 1991)
A dynamic single-equation model for plant interaction is compared with the competition mechanism implicit in larger simulation models. When light is the limiting factor, both mechanisms can be written in the same mathematical form containing a ‘driving force’ and a restriction factor. In the single-equation model the driving force is derived directly from the RGR of a competition-free plant. In more comprehensive models, detailed information on the growth of plant organs has to be generated by submodels. When factors other than light are limiting growth, the representation of competition in crop simulation models is complex; the single-equation model has the same form irrespective of which factor is limiting growth. It is argued that simple dynamic models should be developed for complex processes.